PEMANFAATAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) DALAM MENINGKATAKAN POLA PERTUMBUHAN BAWANG MERAH LOKAL (Allium ascalonicum L) SABU RAIJUA NTT - Laurensius Lehar; Zainal Arifin; Heny M.C. Sine (Partner, 2018)
Red Onion (Allium ascalonicum L.) Sabu Raijua is one of the horticultural crops that is widely consumed by the people of East Nusa Tenggara (NTT) as a mixture of cooking spices and traditional medicines. For household consumption of around 635,700 tons, non-household consumption such asthe manufacturing industry amounting to 719,200 tons, added up to a total of 1.35 million, meaning a deficit for shallots. The purpose of this study was to obtain information about PGPR in increasing the growth pattern of local onion Sabu Raijua. Using Randomized Block Design (RBD) with 5 treatments, namely p0 (control), P1 (5 ml / liter of water / 2 plants), P2 (10 ml / liter of water / 2 plants), P3 (15 ml / liter of water / 2 plants) ), P4 (20 ml / liter of water / 2 plants) and repeated 4 times. The resultsshowed that local red onion plants of Sabu Raijua given PGPR could increase plant height (42, 45 cm), number of leaves (57.57 leaflets per plant), number of tillers per plant (13.89 tillers). The higher concentration of PGPR can increase the growth pattern of local onion Sabu Raijua plants.